Effects of chain flexibility on the properties of DNA hydrogels. Issue 25 (28th April 2016) - Pan, Wei; Wen, Hao; Niu, Lin; Su, Cuicui; Liu, Chenyang; Zhao, Jiang; Mao, Chengde; Liang, Dehai
Abstract : Counterintuitively, the flexible DNA hydrogel shows advantages over the rigid hydrogel in terms of stability, stretchability, and mechanical properties. Abstract : The effect of chain rigidity on the mechanic properties of DNA hydrogels was studied. Counterintuitively, the hydrogel formed by mainly flexible chains exhibited better stability, stretchability, and much mechanical properties than the hydrogel containing only rigid chains. Calculations showed that the crosslinking ratio in the hydrogel formed by flexible chains was about twice that of the hydrogel formed by rigid chains under the same conditions. We attributed this to the ease of conformational adjustment of flexible chains. Incorporation of 25% rigid chains further improved the performance of DNA hydrogel by shrinking the pore size and tuning its distribution.